Energy savings of radiative cooling paints applied to residential buildings. (15th September 2022) - Peoples, Joseph; Hung, Yu-Wei; Fang, Ziqi; Braun, James; Horton, W. Travis; Ruan, Xiulin
Highlights: We develop a high-fidelity radiative cooling model to study cooling energy savings. Our model incorporates multiple weather parameters for real world benefits of RC. We investigate the electricity savings of RC paint on 16 ASHRAE climate zones. The results show up to 22% and 46% electricity savings for the two building types. Abstract: There is a growing need to understand the real-world utility and potential energy savings of radiative cooling (RC) materials. Here, we present a high-fidelity RC model which accounts for pertinent weather factors including: precipitable water, sky clearness, and dynamic convective heat transfer coefficients based on wind speed. We implement our RC model on a single-story residential building to study the impact of RC in all the ASHRAE climate zones in the United States using the 16 DOE recommended representative cities for each climate zone. For each city, we model two building types to explore both the retrofit implementation of RC materials on a typical building in use today, as well as future buildings integration based on the high efficiency building recommendations provided by the DOE. Our results show > 7% and > 12% electricity savings across the United States for the high efficiency building and typical building, respectively. Interestingly, we find the main benefit comes from the material's ability to offset solar gains, while the heat flux from cooling the exterior surface temperature below the ambient is a secondary benefit. Furthermore, warm climates yield the greatest electricity savings of up to 22% and 46% for the high efficiency and typical building, respectively. We observed that warm climates utilize the "full effects" of RC materials as the below ambient cooling of the exterior is sufficient cooling to lower the interior below the set-point temperature, which greatly reduces the cooling energy demand.